Assessing the quality of environmental design of nursing homes for people with dementia: Development of a new tool. (3rd September 2015) - Fleming, Richard; Bennett, Kirsty
<x xml:space="preserve">Abstract</x> Objective To develop an environmental audit tool suitable for use across the spectrum of people with dementia. Method The existing Environmental Audit Tool was supplemented with items describing the environmental needs of people in the final stages of dementia. Two independent raters assessed 30 aged care homes using this draft tool and the Therapeutic Environment Screening Survey for Nursing Homes (TESS‐NH). The Environmental Audit Tool‐High Care, comprising eight sub‐scales with acceptable levels of internal reliability, was constructed. Validity was assessed against the TESS‐NH and the EAT‐HC's ability to differentiate units specifically for people with dementia from other residential care units. Results The EAT‐HC sub‐scales' inter‐rater reliability (ICC) ranged from 0.52 to 0.92. Correlations with the TESS‐NH were highly significant. The EAT‐HC total score differentiated between dementia‐specific homes and others. Conclusion The EAT‐HC can validly and reliably assess environmental features required by a wide range of people with dementia.